Effectiveness of a decision making unit: agriculture education at the high school level - Batchelder, Jennifer, author; Peal, R. Kraig, advisor; Niswender, Gordon, committee member; Whaley, David, committee member; Lacy, Michael G., committee member; Makela, Carole J., committee member (Colorado State University. Libraries, 2004)
Many curriculums and instructors present information in a discipline-based format. In real-life situations, decisions made regarding one area have repercussions that are felt in multiple areas. The purpose of this study was to examine the impact a decision making unit taken from the Integrated Resource Management (IRM) High School Curriculum Aid Compact Disc had on the decision making approach of high school students. Most studies assessing thought processes are based on self-report measures where students indicate their perceived skill level rather than completing tasks which provide evidence of their actual skill level. An objective instrument was developed to assess students' approach to problem solving by allowing them to display their own skills. Student approach to decision making was measured as the variance related to the level of importance students placed on items related to four domain areas (animal science, environment, financial, and human). Eighty-three high school students and 14 instructors participated in the project. While significant interactions between pre and post test administrations were not detected, self report by students indicated their approach to decision making had changed as a result of completing the decision making unit. Student and instructor feedback indicated there is not one right or best way to develop curriculum or deliver instruction. Within one class there are students with diverse learning styles, levels of skill, interests, and prior knowledge. Curriculum packages should be developed and delivered in a manner which addresses multiple learning styles simultaneously and provides instructors with a variety of materials to utilize. Over 90% of responding students were from rural areas. As rural populations continue to decline and core credit requirements placed on high school students increases, agriculture education instructors need to increase the number of non-rural students in their classes in order to ensure the survival of their programs as well as maintain a level of the population that is agriculture literate. While conceptually it makes sense to assess the level of importance students place on various domain areas when facing a decision, there may be better approaches to assess student approach to problem solving. Further research exploring objective approaches to assess thought processes including decision making is needed.
Keywords: curricula; teaching; agricultural education; secondary education; curriculum development